Megnetic Ressonance Angiography Based Comparison of Age-Related Variations in Vascular Diameter of Circle of Willis in Bengali Population of Chattogram Division (Journal of Chittagong Medical College Teachers' Association, 2023)
Background: Magnetic Resonance Angiography (MRA) is a non-invasive and non-radiation dependent most widely used method for detecting the morphology of Circle of Willis (COW). By using the 3D-TOF-MRA the present study was aimed to determine whether there is any differenceof COW vessels diameters between two specified age groups in Bengali population of Chattogram Division.Materials and methods: This cross-sectional observational study was conducted in the department of Anatomy, Chittagong Medical College, Chattogram, upon 60 study subjects (29 were male and 31 were female) by dividing them into two groups (£40 years and >40 years of age). For statistical analysis unpaired student’s t-test was done and p-value was considered significant if it was